A new species of gecko of the genus Cnemaspis Strauch, 1887 from the Western Ghats, India - Mirza, Zeeshan A.; Pal, Saunak; Bhosale, Harshal S.; Sanap, Rajesh V. (Zootaxa, 2014)
A new species of the gekkonid genus Cnemaspis is described from the lateritic plateau of the northern Western Ghats of Maharashtra, western India. The new species is diagnosed by the following suite of characters: small sized Cnemaspis, SVL less than 35 mm (21.52–33.65). Dorsal scales on trunk heterogeneous, granular scales intermixed with large smooth scales and large keeled conical tubercles. Spine-like tubercles absent on flank. Two pairs of postmentals, inner postmentals separated by a single enlarged chin shield. Ventral scales on trunk smooth, imbricate, 26–28 scales across the belly between the lowest rows of dorsal scales. Subdigital scansors smooth, entire, unnotched; lamellae under digit IV of pes 17-20.Males with four femoral pores on each thigh and lacking pre-cloacal pores. Median row of sub-caudals smooth, imbricate and not enlarged. The present discovery highlights the need for dedicated herpetofaunal explorations in the northern Western Ghats to ascertain the exact diversity and distribution of Cnemaspis in India to elucidate the apparent disjunct distribution of the genus in the country.